Pengembangan Media Pembelajaran Berbasis Aplikasi Wolfram Mathematica Pada Materi Fungsi dan Permodelannya - Akbar, Nanang Malik; Satriawati, Gusni; Khairunnisa, Khairunnisa (FIBONACCI: Jurnal Pendidikan Matematika dan Matematika, 2024)
This study aims to explain the process of the development of an instructional media based on a Wolfram Mathematica application for math functions and their graphs. Besides that, this study explains the development of an instructional media based on a Wolfram Mathematica application for math functions and their graphs with valid, practical, and effective value. The method that is used is Research and Development (R&D) with ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. This study of development of an instructional media has been validated by 3 lecturers of The Department of Mathematics Education and by 4 mathematics teachers using the Likert scale with V Aiken Analysis. Moreover, this instructional media has been implemented to 35 students from SMAN 1 Bojonggede. The result from some validators explains that the instructional media has a valid criterion with V Aiken value 0,76. The student response form for the instructional media that has been used explains that the e-module gets a practical criterion with an 82.9% practical value. Therefore, the instructional media based on Wolfram Mathematica application can be used for learning mathematics for math functions and their graphs.